Effect of 26-years of soil tillage systems and winter cover crops on C and N stocks in a Southern Brazilian Oxisol - Tales Tiecher; Elci Gubiani; Maria Alice Santanna; Murilo Gomes Veloso; Ademir Calegari; Lutécia Beatriz dos Santos Canalli; Maria Renate Finckh; Laurent Caner; Danilo dos Santos Rheinheimer (Revista Brasileira de Ciência do Solo, 2020)
ABSTRACT Soil management and crop rotation are key factors in controlling the accumulation of C and N in the soil profile, but their long-term effect remains poorly understood for deep soil layers, especially in subtropical conditions. Using a long-term experiment (26-years), this study aimed to evaluate the effect of different soil management systems associated with different winter cover crops on C and N accumulation in a very clayey (72 % clay) soil up to 1 m deep. Two tillage systems [conventional tillage (CT) and no-tillage (NT)] were cultivated with eight winter cover crops (black oat, rye, common vetch, hairy vetch, oilseed radish, wheat, blue lupine, and fallow) in a subtropical Oxisol from Southern Brazil. Soil samples were taken in eight soil layers up to 1.00 m soil depth after 26 years of experiment and, also from an adjacent native forest. After forest clearing, the C stock in the 0.00-0.20 m soil layer was reduced by 45 % in only 10 years (from 1976 to 1986) of soil tillage. Twenty-six years after the beginning of the experiment, C and N stock in 0.00-0.20 m soil layer were 13 and 20 % higher in NT compared to CT, with the greatest differences in C and N content observed in the 0.00-0.05 m layer. When associated with winter cover crops, NT accumulated 0.6 and 0.06 Mg ha-1 yr-1 more C and N than CT with winter fallow in the 0.00-0.20 m soil layer. No-tillage and CT recovered 95 and 83 %, respectively, of the C stock found in the 0.00-0.20 m layer from the native forest. However, in the 0.00-1.00 m soil layer, the positive effect of NT on soil C accumulation compared to CT was diluted, and no clear effect of NT was verified. Moreover, no difference in winter cover crops on soil C and N stocks were observed in all soil layers, possibly due to their similar residues input (3.3-4.9 Mg ha-1 yr-1). No-tillage associated with high biomass input through winter cover crops promoted a faster recovery of soil C and N stock than in CT and, therefore, is an efficient tool to improve soil C and N accumulation even in Oxisols with high clay content.